Numerical Analysis of Arterial Plaque Thickness and its Impact on Artery Wall Compliance - LJ Vallez; B Sun; BD Plourde; JP Abraham; CS Staniloae (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2015)
Cardiovascular disease is a major cause of mortality throughout the world. The history of cardiovascular research is rich and although this study is not intended to be a review of the subject, a short summary related to the present work is necessary. Interested readers are invited to review articles such as [1-4]. These studies are representative of the literature which deal with the complexities of hemodynamics. Among the important subtopics are the relationship between the wall and the fluid. The fluid exerts a shear stress on the wall which is believed to be a causing of thickening of the wall and the initiation of cardiovascaular disease. The flow also has an impact on transport through the arterial wall [5-20]. In addition to these hemodynamic-focused studies, it has been found that arterial compliance (the distension of an artery wall during the cardiac cycle) is an important indicator of disease progression. In particular, for a diseased artery, the stiffened arterial wall or the rigid plaque layer reduces the otherwise healthy-artery response to pressure fluctuations [21-22]. In addition, the presence of a stenosis can affect the blood velocity profile [21-26] which can be measured Doppler or ultrasound techniques [27-37].